HISTORY OF FORMATION AND PRESENT OF MAKOM ART (Conferencea, 2022)
This article provides detailed information about the history of the origin of the art of status, the stages of the development of the art of status in the society of individuals, the opinions about status in the works of Eastern scientists, and the role of the art of status in human development.